2020
DOI: 10.3389/fchem.2020.00817
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Approaches Towards Useful Photocatalytic Materials

Abstract: The long-standing crusade searching for efficient photocatalytic materials has resulted in a vast landscape of promising photocatalysts, as reflected by the number of reviews reported in the last decade. Virtually all of these reviews have focused on quantitative approaches aiming at developing an understanding of the underlying mechanisms behind photocatalytic behavior and the parameters that influence structure-function correlation. Less attention has been paid, however, to qualitative measures around the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 132 publications
0
10
0
Order By: Relevance
“…Alcohols from bio‐sources are interesting reactant molecules for hydrogen production in the quest to set up a carbon‐neutral and thus environmentally benign process [149] . With a report on qualitative approaches towards useful photocatalytic materials, Parkin and coworkers provided a critical perspective on some of the main factors affecting the assessment of photocatalytic materials with application potential [150] . They conclude that although the area of photocatalysis may have reached maturity from a fundamental perspective, the research efforts in photocatalyst design and engineering are still in their infancy.…”
Section: Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohols from bio‐sources are interesting reactant molecules for hydrogen production in the quest to set up a carbon‐neutral and thus environmentally benign process [149] . With a report on qualitative approaches towards useful photocatalytic materials, Parkin and coworkers provided a critical perspective on some of the main factors affecting the assessment of photocatalytic materials with application potential [150] . They conclude that although the area of photocatalysis may have reached maturity from a fundamental perspective, the research efforts in photocatalyst design and engineering are still in their infancy.…”
Section: Photocatalysismentioning
confidence: 99%
“… [149] With a report on qualitative approaches towards useful photocatalytic materials, Parkin and coworkers provided a critical perspective on some of the main factors affecting the assessment of photocatalytic materials with application potential. [150] They conclude that although the area of photocatalysis may have reached maturity from a fundamental perspective, the research efforts in photocatalyst design and engineering are still in their infancy. Thus, the search for new materials, especially alternatives for TiO 2 , is a field of explorative nature.…”
Section: Photocatalysismentioning
confidence: 99%
“…A disadvantage of large-scale application would be the incorrect choice of catalyst for pollutant degradation. That is, utilizing a photocatalyst that is ineffective or incompatible with the contaminants (Hlongwane et al 2019;Zhang et al 2019;Quesada-Cabrera & Parkin 2020). Xu et al (2019), as shown on Figure 11.…”
Section: Photocatalysts Types and Environmental Impactmentioning
confidence: 99%
“…2 Similarly, within the ongoing green energy transition, unassisted photocatalysis holds out the great promise of providing transformational technologies towards both CO 2 scrubbing and hydrogen fuel production. 1,3 However, due to the highly non-equilibrium nature of photocatalysis and the complexity of its underpinning reactions, being situated at interface been a solid-state semiconductor and a liquid or gas medium, the entire scope of its operation still is not completely understood. 1,3 As with all chemistry, photocatalytic efficiency is fundamentally determined by rate limiting reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 However, due to the highly non-equilibrium nature of photocatalysis and the complexity of its underpinning reactions, being situated at interface been a solid-state semiconductor and a liquid or gas medium, the entire scope of its operation still is not completely understood. 1,3 As with all chemistry, photocatalytic efficiency is fundamentally determined by rate limiting reactions. 4,5 Though fundamental in nature, a deeper understanding of such reaction rates could possibly lead to vast improvements in photocatalytic efficiency and broaden its impact within the nascent green technology transition.…”
Section: Introductionmentioning
confidence: 99%